Pemaknaan dan Simbolisasi Ikan dalam Khazanah Naskah Melayu: Analisis Semiotika Roland Barthes - Putra, Ragil; Buduroh, Mamlahatun (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2023)
Al-Attas in one of his sub-chapters mentions the use of the word 'Ikan Tunggal' (Unique Fish) in one of Hamza Fansuri's works entitled Sha’ir Jawl fasal fl bayan ‘Ilm al-Suluk wa’l-Tawhid.